Computational protein-protein interactions - Russinov, Ruth; Schreiber, Gideon (CRC, 2009)
Often considered the workhorse of the cellular machinery, proteins are responsible for functions ranging from molecular motors to signaling. The broad recognition of their involvement in all cellular processes has led to focused efforts to predict their functions from sequences, and if available, from their structures. An overview of current research directions, Computational Protein-Protein Interactions examines topics in the prediction of protein-protein interactions, including interference with protein-protein interactions and their design.